2011
DOI: 10.1175/2010jas3597.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Charge Distribution in Thunderstorms on Lightning Propagation Paths in Darwin, Australia

Abstract: The charge distributions in a thundercloud play an important role in the initiation and propagation of lightning discharges. To further understand the effects of charge distributions on lightning discharge, the authors conducted a very high-frequency (VHF) lightning observation campaign during the 2006/07 monsoon in Darwin, Australia, using a VHF broadband digital interferometer (DITF). A C-band polarimetric weather radar to estimate the precipitation profiles such as hydrometeor classification was operated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Akita et al [2011] found that the negative leaders of negative CG flashes propagated a horizontal distance about 10 km in cloud first, and then bent to reach ground, but they did not give an explanation.…”
Section: Effect Of Distribution Range Of Lpc Region On Lightning Discmentioning
confidence: 94%
See 1 more Smart Citation
“…Akita et al [2011] found that the negative leaders of negative CG flashes propagated a horizontal distance about 10 km in cloud first, and then bent to reach ground, but they did not give an explanation.…”
Section: Effect Of Distribution Range Of Lpc Region On Lightning Discmentioning
confidence: 94%
“…The propagation behavior of lightning channels and the reason for formation of different types of lightning have been difficult problems in lightning scientific research field for a long time. With the development of modern observation and numerical simulation techniques, numerous studies indicated that lightning types, polarity, and propagation behavior may be closely related to the charge distribution of thunderstorms [e.g., Mazur and Ruhnke 1998;Zhang et al 2006;Krehbiel et al 2008;Zheng et al 2010;Akita et al 2011]. The typical charge distribution of thunderstorms is dipole or tripole charge structure, and the difference between them is whether there is an LPC region [Williams 1989].…”
Section: Introductionmentioning
confidence: 99%
“…VHF DITF is a 2D VHF lightning mapper [Yoshida et al, 2012a] that enables obtaining 3D lightning images when two or more VHF DITFs simultaneously locate one flash [Morimoto et al, 2004;Akita et al, 2010;Yoshida et al, 2010;Akita et al, 2011]. VHF DITFs were operated at Sites 1 and 5 ( Figure 1).…”
Section: Vhf Broadband Digital Interferometer (Vhf Ditf)mentioning
confidence: 99%
“…5, 6, and 9 were negative [13]. Akita and colleagues [26] observed lightning discharges in Darwin, Australia, and reported that IC discharges developed in the upper positive charge regions in thunderstorms. In this study, it seems that positive charges existed in the regions where negative leaders of IC discharges developed.…”
Section: Charge Structure Removed By Ic Dischargementioning
confidence: 99%
“…9. In a thunderstorm, ice pellets are charged positively by the noninductive charging mechanism [26]. In the precipitation radar observations, the radar reflectivity of ice pellet regions is lower than that in graupel or hail regions [27], and thus it is likely that positively charged ice-pellet regions existed in the region where the negative leaders developed.…”
Section: Charge Structure Removed By Ic Dischargementioning
confidence: 99%